Influence of food handlers' compliance with procedures of poultry carcasses contamination: A case study concerning evisceration in broiler slaughterhouses. (October 2016) - Pacholewicz, Ewa; Sura Barus, Sri Aika; Swart, Arno; Havelaar, Arie H.; Lipman, Len J.A.; Luning, Pieternel A.
Abstract: Campylobacter remains the most commonly reported zoonotic agent worldwide. Reducing the concentration of Campylobacter on chicken meat is seen as the most efficient strategy to diminish the number of human campylobacteriosis cases. Analysis of risk factors related to characteristics of broiler batches and processing conditions could, however, not fully explain differences in impact of processing on contamination levels between slaughterhouses. Our study aimed at investigating whether compliance of food handlers with procedures on setting and controlling evisceration process parameters could explain differences in microbial concentrations on carcasses between slaughterhouses. The study was conducted in two commercial broiler chicken slaughterhouses. Analysis of documentation provided insight in the adequacy of procedures, and observational studies revealed insight in compliance with procedures by using a set of criteria for evisceration control. The frequency of carcasses with visible faecal contamination was counted and Escherichia coli concentrations on carcasses classified based on visible contamination was analysed. E . coli was found to be a valid indicator for Campylobacter during evisceration. Food handlers' knowledge, attitude and practices related to evisceration control tasks were analysed based on a validated questionnaire. Documentation analysis revealed obvious differences in the procedures between slaughterhouses. The observation study revealed that in the slaughterhouse with advanced procedures, the food handlers more often complied with these procedures and a lower frequency of carcasses with visible faecal contamination was observed. Carcasses contaminated with visible faecal spots, even at a low level, carried significantly higher concentrations of E . coli than visibly clean carcasses. Food handlers in both slaughterhouses revealed a good knowledge level. The attitude of food handlers differed between slaughterhouses. In one slaughterhouse, where food handlers complied more frequently with procedures their attitude was at a good level, and practices at good and moderate levels. In the other slaughterhouse the attitude of food handlers was at moderate level and practices at moderate and poor levels. In conclusion, the results from our case study suggest that management factors like availability of adequate monitoring procedures and food handlers' compliance with these procedures may influence the bacterial concentrations on carcasses. Our study demonstrated that compliance with procedures differed between slaughterhouses, and might be associated with faecal contamination of carcasses and thus with higher bacterial concentrations. These results suggest that managerial improvements, supervising and motivating food handlers could be an important control point. To validate the observed relation between compliance with procedures and contamination of carcasses, an intervention study is needed. Highlights: The frequency of carcasses contaminated with faeces differed between slaughterhouses. The frequency was associated with compliance with evisceration controls. Carcasses with visible faecal contamination carried higher concentrations of E . coli . Managerial aspects create an area to intervene while improving broiler processing hygiene.